Metabolic Reprogramming, Gut Dysbiosis, and Nutrition Intervention in Canine Heart Disease - Li, Qinghong (Frontiers in Veterinary Science, 2022)
This review provides a state-of-the-art overview on recent advances in systems biology in canine cardiac disease, with a focus on our current understanding of bioenergetics and amino acid metabolism in myxomatous mitral valve disease (MMVD). Cross-species comparison is drawn to highlight the similarities between human and canine heart diseases. The adult mammalian heart exhibits a remarkable metabolic flexibility and shifts its energy substrate preference according to different physiological and pathological conditions. The failing heart suffers up to 40% ATP deficit and is compared to an engine running out of fuel. Bioenergetics and metabolic readaptations are among the major research topics in cardiac research today. Myocardial energy metabolism consists of three interconnected components: substrate utilization, oxidative phosphorylation and ATP transport and utilization. Any disruption or uncoupling of these processes can result in deranged energy metabolism and heart failure (HF). The review describes the changes occurring in each of the three components of energy metabolism in MMVD and heart failure. It also provides an overview on the changes in circulating and myocardial glutathione, taurine, carnitines, branched-chain amino acid catabolism and tryptophan metabolic pathways. In addition, the review summarizes the potential role of the gut microbiome in MMVD and heart failure. As our knowledge and understanding in these molecular and metabolic processes increase, it becomes possible to use nutrition to address these changes and to slow the progression of the common heart diseases in dogs.